First International Conference on Industrial and Information Systems 2006
DOI: 10.1109/iciis.2006.365753
|View full text |Cite
|
Sign up to set email alerts
|

Always Best-Connected QoS integration model for the WLAN, WiMAX Heterogeneous Network

Abstract: This paper proposes a mechanism that supports Always Best-Connected (ABC) Quality of service (QoS) to the application in a heterogeneous network. The heterogeneous network consists of IEEE 802.11e WLAN and IEEE802.16d WiMAX access networks. The User Equipment (UE) in the network is enabled with both WLAN and WiMAX access capabilities. The Generic Virtual Link Layer (GVLL) is placed above the WLAN and WMANMAC layer in the UE, decides the best serving access network in terms of QoS support. The best access netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The exact mechanism of how it is achieved is not discussed in the paper. In [23], the authors used packet loss and delay as critera for performing handoff from one network to another. The authors reported 9 ms maximum delay which is not possible in WiMax without altering default parameters.…”
Section: Related Workmentioning
confidence: 99%
“…The exact mechanism of how it is achieved is not discussed in the paper. In [23], the authors used packet loss and delay as critera for performing handoff from one network to another. The authors reported 9 ms maximum delay which is not possible in WiMax without altering default parameters.…”
Section: Related Workmentioning
confidence: 99%
“…Song et al [7] researched user association in the cellular-WLAN heterogeneous network, and users always first try to access WLAN to obtain higher data rate, which is referred to as WLAN-first scheme. References [8,9] focus on the network selection strategy in the WiMAX-WLAN heterogeneous network, and users always try to select access points that can support the highest rate-namely, the best AP selection algorithm.…”
Section: Introductionmentioning
confidence: 99%